Post-trial Access in Maternal Vaccine Trials - Van Roessel, I. M. A. A.; Mazur, N. I.; Shah, S. K.; Bont, L.; Van Der Graaf, R. (American Journal of Perinatology, 2019)
Provisions for post-trial access (PTA) of the experimental intervention are required before the start of a clinical trial. Although there has been ample attention for PTA in the context of preventive vaccine research, discussions on PTA barely include maternal vaccine trials in which mother–infant pairs are exposed to the intervention. In maternal vaccination trials, specific PTA arrangements are required because pregnancy is transient and PTA may apply to the next pregnancy or the child. In this article, we examine the application and adherence to PTA in the context of maternal vaccine trials. We focused on differences between publications before and after 2000 when international ethical guidance documents formalized PTA requirements. Randomized maternal vaccine trials were included after a systematic search for clinical trials in phases II and III with a maternal vaccine as intervention. We used PTA as defined at the time of publication in the World Medical Association's Declaration of Helsinki (DoH) or in the ethical guidelines of the Council for International Organizations of Medical Sciences (CIOMS). In addition, we investigated whether PTA was included in the trial design. Therefore, we contacted principal investigators (PI’s) of the publications found in the review to fill out a questionnaire regarding provisions for PTA. Before and after 2000, no trial articles examined in the systematic review described PTA in their trial publication (0/7, 0% and 0/17, 0%, respectively). In addition, more than half of the PI’s of the trials found were not familiar with PTA recommendations in international ethical guidelines. Most cases of PTA included making knowledge available by publishing the results of the trial. The revision of the DoH in 2002 and the CIOMS ethical guidelines in 2002 has not resulted in increased PTA provisions for maternal vaccination trials. PTA is a shared responsibility of various stakeholders including sponsors, Institutional Review Boards, regulators, political entities, and researchers. Inclusion of PTA provisions in trial protocols and publications on maternal vaccination trials is essential to increase transparency on the form and content of these provisions.
Keywords: post-trial access; maternal vaccination; vaccine trials; research; ethical